Recent Advances in Antibody Discovery Using Ultrahigh-Throughput Droplet Microfluidics: Challenges and Future Perspectives - Dhiman Das; John Scott McGrath; John Hudson Moore; Jason Gardner; Daniël Blom (Biosensors)
Droplet microfluidics has emerged as a transformative technology that can substantially increase the throughput of antibody “hit” discovery. This review provides a comprehensive overview of the recent advances in this dynamic field, focusing primarily on the technological and methodological innovations that have enhanced the antibody discovery process. This investigation starts with the fundamental principles of droplet microfluidics, emphasizing its unique capabilities for precisely controlling and manipulating picoliter-volume droplets. This discussion extends to various assay types employed in droplet microfluidics, including binding assays, functional assays, Förster Resonance Energy Transfer (FRET) assays, internalization assays, and neutralization assays, each offering distinct advantages for antibody screening and characterization. A critical examination of methods to improve droplet encapsulation is presented, besides addressing challenges such as reducing the leakage of small molecules from droplets and explaining what a “hit” droplet looks like. Furthermore, we assess design considerations essential for implementing high-throughput fluorescence-activated droplet sorting (FADS) workstations and emphasize the need for automation. This review also delves into the evolving commercial landscape, identifying key market players and emerging industry trends. This review paper aims to catalyze further research and innovation, ultimately advancing the field towards more efficient and robust solutions for antibody identification and development.